Implementation of Religious Moderation in the Non-Formal Education in Forming a Multicultural Society - Turhamun (International Journal of Social Science and Religion (IJSSR), 2024)
Sharia has taught moderation through several verses in the Qur'an, such as surah Al-Baqarah verse 256 and surah Yunus verse 99. Meanwhile, Prophet Muhammad taught moderation during his stay in Medina, as stated in the Medina Charter. This charter has given enough space for non-Muslims to worship without interference. Today, moderation is often preached at both institutional and cultural levels. However, its implementation is usually a dead end. Therefore, this study aims to analyze the implementation of moderation in shaping a multicultural society. The results of this study show that religious implementation can start from the most minor institutions, such as TPQ and family. In addition, religious moderation is also the basis of cultural life because moderation will bring justice, balance, and compassion. The implementation of religious moderation within the framework of a multicultural society must be done from an early age. Good habituation will form a good and strong character that is shown by mutual respect, appreciation of differences, and love for the nation and state. Among the habits to form a moderate character are memorizing short letters that explain the interpretation of bismillah, praying in the congregation as a symbol of unity and integrity, then for confirmation of faith, and khatmil Quran, which begins with singing the national anthem.